2016
DOI: 10.3390/rs8110964
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Diffuse Attenuation of Photosynthetic Active Radiation and Its Main Regulating Factors in Inland Waters of Northeast China

Abstract: Light availability in lakes or reservoirs is affected by optically active components (OACs) in the water. Light plays a key role in the distribution of phytoplankton and hydrophytes, thus, is a good indicator of the trophic state of an aquatic system. Diffuse attenuation of photosynthetic active radiation (PAR) (K d (PAR)) is commonly used to quantitatively assess the light availability. The PAR and the concentration of OACs were measured at 206 sites, which covered 26 lakes and reservoirs in Northeast China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 52 publications
(53 reference statements)
1
14
0
2
Order By: Relevance
“…Otros estudios recientes muestran a la turbidez como el principal factor que afecta a ambas propiedades ópticas. Así, en 26 lagos y embalses del noreste de China el principal factor que explica las variaciones en K d (que osciló entre 0.45 y 15.04 m -1 ) fue la turbidez y solamente en lagos excepcionalmente claros se encuentra que K d dependa de la Clorofila o de la materia orgánica disuelta de naturaleza cromofórica (Ma et al, 2016). Igualmente en el trabajo de Borowiak y Borowiak (2016), citado previamente, también la turbidez fue la variable que mejor explicó la variación en K d .…”
Section: Variables Determinantes De K D Y Sdunclassified
“…Otros estudios recientes muestran a la turbidez como el principal factor que afecta a ambas propiedades ópticas. Así, en 26 lagos y embalses del noreste de China el principal factor que explica las variaciones en K d (que osciló entre 0.45 y 15.04 m -1 ) fue la turbidez y solamente en lagos excepcionalmente claros se encuentra que K d dependa de la Clorofila o de la materia orgánica disuelta de naturaleza cromofórica (Ma et al, 2016). Igualmente en el trabajo de Borowiak y Borowiak (2016), citado previamente, también la turbidez fue la variable que mejor explicó la variación en K d .…”
Section: Variables Determinantes De K D Y Sdunclassified
“…Light is one of the most important factors governing primary production and photosynthesis in the aquatic ecosystems (Kirk, 1994;Ma & Song & Wen & Zhao & Shang & Fang & Du, 2016;Song & Ma & Wen & Fang & Shang & Zhao & Wang & Du, 2017). Light availability plays a crucial role in the distribution of phytoplankton and hydrophytes, and it is also a good indicator of the trophic state of an aquatic system.…”
Section: Introductionmentioning
confidence: 99%
“…However, Environmental change and anthropogenic activity have made it challenging to accurately assess Kd patterns in the extremely turbid inland waters (Zheng & Ren & Li & Huang & Liu & Du & Lyu, 2016). The comprehensive analysis of the relationships between Kd(PAR) and aOACs is an imperative requirement to retrieve Kd(PAR) from remote sensing data for turbid inland waters (Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al [5] reported the spatial distribution of the diffuse attenuation coefficient of photosynthetic active radiation (PAR) (K d (PAR)) and its main regulating factors in 26 lakes and reservoirs in Northeast China. The results showed that total suspended matter was the dominant factor in determining K d (PAR) values and best correlated with K d (PAR).…”
Section: Highlights Of Research Articlesmentioning
confidence: 99%